2021
DOI: 10.1039/d1sc03011f
|View full text |Cite
|
Sign up to set email alerts
|

Reversible redox controlled acids for cationic ring-opening polymerization

Abstract: Advancements in externally controlled polymerization methodologies have enabled the synthesis of novel polymeric structures and architectures, and they have been pivotal to the development of new photocontrolled lithographic and 3D...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…1 H NMR (500 MHz, CDCl 3 ):  = 4.89 (dhept, J = 6.3, 6.2 Hz, 1 H, CHMe 2 ), 4.77 (t, J = 2. 1 Hz,1 H,H3),4.50 (dhept,J = 8.4,6.2 Hz, 1 H, CHMe 2 ), 4.35 (t, J = 2.6 Hz, 1 H, H4), 4.26 (s, 5 H, Cp), 1.49 (d, J = 6.1 Hz, 6 H, CHMe 2 ), 1.30 (d, J = 6.2 Hz, 3 H, CHMe 2 ), 1.09 (d, J = 6.2 Hz, 3 H, CHMe 2 ), 0.35 (s, 9 H, SiMe 3 ).…”
Section: Feature Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…1 H NMR (500 MHz, CDCl 3 ):  = 4.89 (dhept, J = 6.3, 6.2 Hz, 1 H, CHMe 2 ), 4.77 (t, J = 2. 1 Hz,1 H,H3),4.50 (dhept,J = 8.4,6.2 Hz, 1 H, CHMe 2 ), 4.35 (t, J = 2.6 Hz, 1 H, H4), 4.26 (s, 5 H, Cp), 1.49 (d, J = 6.1 Hz, 6 H, CHMe 2 ), 1.30 (d, J = 6.2 Hz, 3 H, CHMe 2 ), 1.09 (d, J = 6.2 Hz, 3 H, CHMe 2 ), 0.35 (s, 9 H, SiMe 3 ).…”
Section: Feature Synthesismentioning
confidence: 99%
“…For instance, their hydrolysis furnishes the corresponding ferrocenephosphonic acids, 3a 4 used as precursors of metal complexes 5 or as redox-active polymerization catalysts. 6 On the other hand, their reduction represents a practical access to primary phosphines, 7 and therefore to original phosphorus-based functional groups 8 and ligands for catalytic transformations. 7a 9…”
Section: Table 1 Optimization Of the Cu-promoted Hirao ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of potentiostatic coulometry or chronoamperometry offers specific advantages in addition to temporal control, such as tuning the extent of the electron transfer process and alleviating the need for the repeated addition of chemical redox reagents. , Electrochemical control of polymerization reactions has been demonstrated previously; the first example was reported in 2011 by Matyjaszewski and co-workers, who used an electric current to toggle reversibly an on/off atom transfer radical polymerization (ATRP) reaction mediated by a copper­(I)/copper­(II) redox couple . Recently, electrochemically controlled polymerizations by mechanisms different from ATRP have been reported. However, electrochemical control of ring-opening polymerization (ROP) has garnered less attention than that of cationic or radical polymerizations. ROP typically employs metal catalysts that offer good control and can be used to produce a wide variety of polymers, including polyesters, polyethers, and polycarbonates …”
Section: Introductionmentioning
confidence: 99%
“…In another example, Fors et al reported a ferrocenyl acid that could be switched on and off for lactone (δ-valerolactone, VL, and ε-caprolactone, CL) polymerization (Figure b) . A decrease in p K a upon oxidation leads to activation of the monomer via protonation, and then polymerization.…”
Section: Introductionmentioning
confidence: 99%